Comparative Politics : Rationality, Culture, and Structure - LICHBACH, Mark Irving (Cambridge University Press, 1997)
Comparative Politics: Rationality, Culture, and Structure examines the major research traditions in comparative politics, assessing knowledge, advancing theory, and in the end seeking to direct research in the coming years. It begins by examining the three research schools that guide comparative politics: rational choice theory, culturalist analysis, and structuralist approaches. Margaret Levi, Marc Howard Ross, and Ira Katznelson offer briefs for each of the schools, presenting core principles, variations within each approach, and fresh combinations. A second set of authors then applies the research traditions to established fields of scholarship. Samuel H. Barnes examines work on mass politics, Doug McAdam, Sidney Tarrow, and Charles Tilly synthesize studies of social movements and revolutions, Peter A. Hall contrasts new research on the political economy of established democracies, and Joel S. Migdal offers a new approach to studies of the state